2017
DOI: 10.1088/1361-648x/aa9a00
|View full text |Cite
|
Sign up to set email alerts
|

Electron trap states at InGaAs/oxide interfaces under inversion through constant Fermi-levelab initiomolecular dynamics

Abstract: We employ constant-Fermi-level ab initio molecular dynamics to investigate defects at the InGaAs/oxide interface upon inversion. We adopt a substoichiometric amorphous model for modelling the structure at the interface and investigate the formation of defect structures upon setting the Fermi-level above the conduction band minimum. The defect formation is detected through both an analysis of the atomic structure and a Wannier-decomposition of the electronic structure. This computer driven approach is able to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The occurrence of the In-In bond indicates the agglomeration of In elements. The bond lengths of In-In, In-Ga and Ga-Ga in the present work are about 2.32, 2.14 and 2.12 Å, while Bouzid's ab initio calculation [38] shows that the bond lengths of In-In, In-Ga and Ga-Ga are 2.70, 2.56 and 2.43 Å. Both of the results show that the bond length of In-In is larger than In-Ga, while the bond length of In-Ga is larger than Ga-Ga.…”
Section: Defect Accumulation In Inxga 1−x Nmentioning
confidence: 42%
See 1 more Smart Citation
“…The occurrence of the In-In bond indicates the agglomeration of In elements. The bond lengths of In-In, In-Ga and Ga-Ga in the present work are about 2.32, 2.14 and 2.12 Å, while Bouzid's ab initio calculation [38] shows that the bond lengths of In-In, In-Ga and Ga-Ga are 2.70, 2.56 and 2.43 Å. Both of the results show that the bond length of In-In is larger than In-Ga, while the bond length of In-Ga is larger than Ga-Ga.…”
Section: Defect Accumulation In Inxga 1−x Nmentioning
confidence: 42%
“…It has been observed in experiments that the In element in InGaN tends to agglomerate during the growth of InGaN materials [37]. In addition, Bouzid and Pasquarello [38] employed constant-Fermi-level ab initio MD to investigate the InGaAs/oxide interface structure and the results showed that metallic In-In, In-Ga and Ga-Ga bonds could be found in InGaAs. In figure 7, the In-In, In-Ga and Ga-Ga partial pair correlation functions of crystalline and amorphized In 0.3 Ga 0.7 N are plotted.…”
Section: Defect Accumulation In Inxga 1−x Nmentioning
confidence: 99%
“…However, one of the most critical problems that must be solved to realize III-V MOSFETs is the formation of a stable MOS interface with low trap density [7]. Compared with the SiO 2 /Si system, the III-V native oxides negatively affect fermi-level pinning and current drift [8][9][10]. The atomic layer deposited (ALD) Al 2 O 3 dielectric in surface InGaAs channel MOSFETs can achieve a thermally stable interface and large band offsets, as confirmed by the previous research on the dielectric layer of InGaAs MOSFETs [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In the constant Fermi level scheme, the mass of the fictitious charge degrees of freedom is set to M e = 100 a.u. The fictitious electronic temperature is controlled by a velocity rescaling method and is set to T e = 30 K. Gaussian-smeared occupations with widths of at most 0.10 eV are used to prevent numerical instabilities[27,33,34,26]. In the present dynamics, the inertial mass is set in such a way that the fluctuations of the grand canonical potential occur on a time scale that accompanies the struc-tural rearrangements, to account for smooth transitions upon charge variations in the physical system.…”
mentioning
confidence: 99%
“…The constant Fermi level molecular dynamics [27,33,34,26] in this work relies on a description of the electronic structure within density functional theory (DFT) through an optimized rVV10 functional [35,36,37]. In the rVV10 functional used in this work, the b parameter is set to 9.3 to ensure a good description of the water density [37].…”
mentioning
confidence: 99%